2015
DOI: 10.1002/zaac.201500542
|View full text |Cite
|
Sign up to set email alerts
|

A New N‐Trityl‐Substituted Aminopyridinato Titanium Catalyst for Hydroamination and Hydroaminoalkylation Reactions – Unexpected Intramolecular C–H Bond Activation

Abstract: Sterically demanding 2,6-bis(tritylamino)pyridine is used for the synthesis of a mono(2,6-diaminopyridinato) titanium complex that undergoes unexpected intramolecular C-H bond activation to give access to an unusual 1-titanaisoindoline derivative. Both titanium complexes do not show high catalytic activity for hydroaminoalkylation reactions of alkenes but exceptional results are obtained in the field of * Prof. Dr. S. Doye 2071 alkene, alkyne, and allene hydroamination including room temperature activity for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…Intriguingly, the use of the aminopyridinato based catalyst IVa , [4e] which was inactive in the corresponding reaction with N ‐methylaniline ( 1 a ), showed significant conversion of N ‐benzylaniline ( 1 b ) and formation of the desired coupling products 4 b and 4 l in a ratio of 93:7 (GC analysis, Figures S64 and S65) in favor of the branched product (Scheme 3). Noteworthy, in the case of sterically more demanding catalyst IVb , [4f] there is no conversion of the starting material 1 b (Figure S66). On the other hand, usage of the formamidinato based catalysts V and VI resulted in the conversion of 1 b but also in the formation of undesired by‐products (Figures S67 and S68), so that catalyst system IVa proved to be best for this transformation.…”
Section: Methodsmentioning
confidence: 99%
“…Intriguingly, the use of the aminopyridinato based catalyst IVa , [4e] which was inactive in the corresponding reaction with N ‐methylaniline ( 1 a ), showed significant conversion of N ‐benzylaniline ( 1 b ) and formation of the desired coupling products 4 b and 4 l in a ratio of 93:7 (GC analysis, Figures S64 and S65) in favor of the branched product (Scheme 3). Noteworthy, in the case of sterically more demanding catalyst IVb , [4f] there is no conversion of the starting material 1 b (Figure S66). On the other hand, usage of the formamidinato based catalysts V and VI resulted in the conversion of 1 b but also in the formation of undesired by‐products (Figures S67 and S68), so that catalyst system IVa proved to be best for this transformation.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent experiments performed with the second‐generation titanium catalysts I , II , and III (Figure ) at temperatures between 140 and 160 °C then revealed that in comparison to [Ind 2 TiMe 2 ], these catalysts favor the formation of the monoalkylated product 2 a with better selectivities (Table , entries 4–11). In this context, the finding that the dialkylated product 3 a was not formed at all in the presence of the sterically crowded trityl‐substituted mono(aminopyridinato) catalyst II deserves particular attention (Table , entry 5).…”
Section: Methodsmentioning
confidence: 99%
“…To further study the scope and especially the limitations of the hydroaminoalkylation of ethylene, we next performed a number of corresponding experiments with secondary amines, which are all known to usually react sluggishly with sterically more demanding 1‐alkenes or styrenes (Table ) . Unfortunately, during this study, it was first found that reactions of ethylene with the N ‐alkylanilines 2 a and 4 possessing alkyl substituents larger than a methyl group do not give better results than reported for corresponding reactions of other alkenes (Table , entries 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
“…After the expected 1,3‐diamine 12 had successfully been obtained in 92 % yield, the allylanilines 8 – 10 possessing an ortho ‐halogen substituent, which offers the possibility of a subsequent Buchwald–Hartwig amination, were also reacted with 11 under identical conditions. Although in the past, the use of other titanium catalysts often led to significantly decreased yields when halogenated substrates were used as starting materials,,, both the ortho ‐chloro‐ N ‐allylaniline 8 and the corresponding bromo substituted compound 9 gratifyingly underwent smooth hydroaminoalkylation reactions in the presence of I to give the corresponding branched products 13 and 14 in 87 and 73 % yield, respectively (Table , entries 2 and 3). On the other hand, the analogous iodo substituted N ‐allylaniline 10 did not react successfully (Table , entry 4).…”
Section: Figurementioning
confidence: 99%